Texas labor history - Glasrud, Bruce A.; Maroney, James C., 1936- (Centennial series of the Association of Former Students, Texas A & M University, 2013)
Too often, observers and writers of Texas history have accepted assumptions about labor movements in the state - both organized and not - that do not bear up under the light of careful scrutiny. Offering a scholarly corrective to such misplaced suppositions, the studies in this book provide a helpful source for scholars and teachers who wish to fill in some of the missing pieces. Tackling a number of such presumptions - that a viable labor movement never existed in the Lone Star State; that Black, brown, and white laborers, both male and female, were unable to achieve even short-term solidarity; that labor unions in Texas were ineffective because of laborers’ inability to confront employers - the editors and contributors to this volume lay the foundation for establishing the importance of labor to a fuller understanding of Texas history. They show, for example, that despite differing working conditions and places in society, many workers managed to unite, sometimes in multi-racial efforts, to overturn the top-down strategy utilized by Texas employers. This collection also facilitates an understanding of how the state’s history relates to, reflects, and differs from national patterns and movements.